FIQH AL-AQALLIYYAH AND MUSLIM MINORITIES IN A NON-MUSLIM COMMUNITY - Adegoke, Kazeem Adekunle (Jurnal Syariah, 2021)
This study researches into the legal theory of fiqh al-aqaliyyah and Muslim minorities in a contemporary non-Muslim community. In order to achieve this objective, the paper examines the fiqh al-aqalliyyah, its legal position in Islamic jurisprudence, its legal instruments and its applicability to lessen the physical, social, financial and emotional hardships or difficulties encountered by Muslim minorities who find themselves in an unfamiliar non-Muslim environment. Research method used in this study is expository, descriptive and analytical in order to showcase the applicability of fiqh al-aqalliyyah in the modern legal theory within the context-specific and needs-based neo-ijtihād legal rulings for Muslim minorities. Conclusively, the paper makes findings that context-specific and needs-based neo-ijtihād legal rulings of fiqh al-aqalliyyah is still viable in this contemporary period to arrest new jurisprudential challenges facing the Muslim minorities in non-Muslim communities. Also neo-ijtihād exercise of fiqh al-aqalliyyah from a competent Islamic jurists and legal theorists of a particular society is meant for that society only and should not be given general or universal application so as not to cause confusion in the context-specific and needs-based jurisprudential response. Finally, the study recommends that Muslim minorities should make use of the Islamic jurists and legal theorists’ neo-Ijtihād exercise of fiqh al-aqaliyyah which are peculiar to their environment in procuring solutions to some of the contemporary Islamic jurisprudential challenges facing them in the non-Muslim community.